Preparation of Reduced Graphene Oxide Films with High and Uniform Thickness for Electromagnetic Interference Shielding - Meng Li; Li-Jing Xie; Zong-Lin Yi; Dong Liu; Zheng Wang; Ruo-Han Niu; Hui Jia; Qing-Qiang Kong (Crystals, 2024)
Reduced graphene films have attracted widespread commercial interest due to high electrical conductivity toward (EMI) shielding. At present, the preparation path of reduced graphene film is to use graphene oxide (GO) as the raw material through self-assembly and high-temperature heat treatment. However, the thickness of reduced graphene films is not high and uniform because of the higher mobility of the graphene oxide slurry, which destroys the reliability of the membrane in the field of electromagnetic interference shielding. Here, we propose the use of sodium carboxymethyl cellulose (CMC) to increase the viscosity of graphene oxide to prepare reduced graphene films with high and uniform thickness. After modification with sodium carboxymethyl cellulose, the EMI shielding effectiveness (EMI SE) of reduced graphene oxide films stabilized at 91–96 dB at 8–12 GHz, which is higher than pure graphene films. Meanwhile, the addition of CMC does not affect the structure of reduced graphene films. This work broadens the application of reduced graphene films in electromagnetic shielding.